Development and evaluation of an ovarian hormone profile classification tool for female athletes: step one of a two-step process to determine ovarian hormone profiles - Alan McCall; Stuart M Phillips; Kirsty J Elliott-Sale; Rachel Harris; Richard J Burden; Georgina K Stebbings; Alysha C D'Souza; Clare Minahan; Thomas Dos’Santos; Tessa R Flood; Laurence P Birdsey; Nigel T Cable; et al. (BMJ Open Sport & Exercise Medicine)
Objective This study aimed to develop a reliable, comprehensive and fit-for-purpose tool for classifying ovarian hormone profiles (OHPs) (step one of a two-step process) in postmenarcheal to perimenopausal female athletes.Methods The OHP classification tool was designed by a team of sport scientists, practitioners and medics and is intended for use by sport practitioners. It incorporates self-reported data and guides subsequent verification methods. Written feedback was received from practitioners currently working with elite female athletes (n=5), ensuring its applicability in an applied sport setting. In addition, inter-user (n=2) and intra-user (n=30) repeatability was assessed.Results All practitioners agreed that the online tool was user-friendly. Four (out of five) practitioners stated they would include the tool in their practice, with the fifth stating that they did not have the capacity to incorporate it in their practice at present. The OHP classification tool showed excellent test–retest reliability with Cronbach’s alpha values exceeding 0.9.Conclusion This tool facilitates the classification of OHPs and promotes discussions between athletes and practitioners, enhancing understanding and management of ovarian hormone health in sportswomen.